The entrepreneurial university and the region: what role for entrepreneurship departments?. Issue 9 (2nd September 2018) - Pugh, Rhiannon; Lamine, Wadid; Jack, Sarah; Hamilton, Eleanor
ABSTRACT: This paper investigates the concept of the entrepreneurial university by examining roles of academic entrepreneurship departments in driving regional economic development outcomes. While a wealth of research investigates the role, activities and function of the entrepreneurial university, very little which focuses specifically on academic entrepreneurship departments, where much of the research, teaching and knowledge exchange concerning entrepreneurship takes place. Two case studies of large and active entrepreneurship departments are presented to illustrate the different roles and activities they undertake in the sphere of economic development in their regions or locales. A dual model of engagement is proposed, whereby the entrepreneurship department operates within the framework of the entrepreneurial university, but also as a regional actor in its own right.